Application of electrical capacitance tomography in circulating fluidised beds – A review. (25th July 2020) - Wang, Haigang; Yang, Wuqiang
Graphical abstract: Application of ECT in gas-solids circulating fluidised bed. Highlights: Application of electrical capacitance tomography in gas-solids fluidised bed are reviewed. ECT sensor design and image reconstruction are discussed. Gas-solids flow dynamics characteristics, solids concentration and bubble characteristics are given. Solids mas flux measurement by cross-correlation method is analysed. Process fault diagnose and process control are discussed. Abstract: Circulating fluidised beds (CFBs) are developed for clean coal combustion and coal gasification, and they play an important role in power generation. With the increase in dimension and thermal capacity, the gas-solids flow dynamics in CFBs becomes more complex. In particular, it is challenging to remain high efficiency in gas-solids separation and circulation. The gas-solids flow inside a CFB chamber is a multi-scale system both in time and space. Because the gas-solids flow dynamics affects the coal combustion efficiency and pollution emission, it is important to investigate the flow dynamics by advanced measurement technology for the design and scaling-up. Electrical capacitance tomography (ECT) has been used for this purpose for two decades. This paper reviews the application of ECT in CFBs for boiler design and clean coal combustion, including optimisation of the furnace structure, boiler dimension, and cyclone arrangement. The principle of ECT including image reconstruction algorithms is briefly introduced. Key issues for application of ECT in CFBs are discussed, including sensor design and data analysis. Then, typical applications related to CFBs are described, including scaling-up of CFB boilers, flow regime identification, characterisation of gas-solids flow dynamics, process fault diagnosis, external solids mass flux measurement and optimisation of processes based on the information obtained by ECT. Some cases related to coal gasification and combustion processes are given and analysed. In the end of the paper, conclusions and the future application of ECT in real coal combustion processes in CFBs are discussed.